2018
DOI: 10.1007/978-981-10-4870-8
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oil based Bio-lubricants and Transformer Fluids

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Among the rare-earth compounds studied, the most widely used elements were La and Ce. Such compounds can be used either individually as lubricant additives or in other NPs such as TiO 2 3 , and LaF 3 NPs used as FMs in lubricants have been widely studied [153][154][155]. Cerium oxide (≈ 90 nm) should also be noted, which was blended in paraffin oil and used as a nanolubricant [156].…”
Section: Rare-earth Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the rare-earth compounds studied, the most widely used elements were La and Ce. Such compounds can be used either individually as lubricant additives or in other NPs such as TiO 2 3 , and LaF 3 NPs used as FMs in lubricants have been widely studied [153][154][155]. Cerium oxide (≈ 90 nm) should also be noted, which was blended in paraffin oil and used as a nanolubricant [156].…”
Section: Rare-earth Compoundsmentioning
confidence: 99%
“…Recently, the use of nanomaterials as lubricant additives (also known as nanolubricants) has become an important research area [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The nanolubricant approach is used to overcome the drawbacks of conventional anti-wear and anti-friction additives associated with the need for chemical reactions with substrates, and hence the induction period for obtaining a tribo-film on the friction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have shown that the acidity of esters increases proportionally overtime, and this increase could extend well beyond the specified limit value, even in an enclosed environment with minimal oxygen. [30], [31]. Better aging performance of cellulose has been found in natural ester with a high level of acidity compared to mineral oil [30].…”
Section: Tablementioning
confidence: 99%
“…The biodegradation of TME oil is 82.2% after 28 days. The biodegradation of NEOs is more than 85% [22]. FR3 oil is produced from soybean oil.…”
Section: B Biodegradability Of Productsmentioning
confidence: 99%